Methodism and the southern mind, 1770-1810 - Lyerly, Cynthia Lynn, 1960- (Religion in America series (Oxford University Press), 1998)
Early Methodism was a despised and outcast movement that attracted the least powerful members of Southern societyslaves, white women, poor and struggling white men - and invested them with a sense of worth and agency. Methodists created a public sphere where secular rankings, patriarchal order, and racial hierarchies were temporarily suspended. Because its members challenged Southern secular mores on so many levels, Methodism evoked intense opposition, especially from elite white men. Methodism and the Southern Mind analyzes the public denunciations, domestic assaults on Methodist women and children, and mob violence against black Methodists. These attacks, Lynn Lyerly argues, served to bind Methodists more closely to one another; they were sustained by the belief that suffering was salutary and that persecution was a mark of true faith. -- Provided by publisher.